High intensity training and energy production during 90-second box jump in junior alpine skiers - Gross, M.; Hemund, K.; Vogt, M. (The Journal of Strength and Conditioning Research, 2014)
Alpine ski races can last up to 2.5 minutes and have very high metabolic demands. One limiting factor for performance is insufficient aerobic energy supply. We studied the effects of an 8-day interval training block on aerobic capacity (VO2max) and performance and physiology during the 90-second box jump test (BJ90), a maximal performance test employed to simulate the metabolic demands of alpine ski racing, in elite junior skiers. After 10 high-intensity interval training sessions, performed as cycling, running, or an obstacle course, VO2max increased in all subjects by 2.5 ± 1.9 ml/minute/kg (4.3 ± 3.2%), as did maximal blood lactate concentration in a graded cycling test (before: 11.7 ± 1.3 mmol/L, after: 14.8 ± 1.8 mmol/L, both parameters p < 0.05). Performance (total jumps) and aerobic energy contribution (63.3 ± 2.8%) during the BJ90 did not increase as hypothesized; however, subjects altered their pacing strategy, which may have counteracted such an effect. Additionally, the present data support the practicality of the performance test used for mimicking the demands of alpine skiing.